2021
DOI: 10.1371/journal.pcbi.1008735
|View full text |Cite
|
Sign up to set email alerts
|

From heterogeneous healthcare data to disease-specific biomarker networks: A hierarchical Bayesian network approach

Abstract: In this work, we introduce an entirely data-driven and automated approach to reveal disease-associated biomarker and risk factor networks from heterogeneous and high-dimensional healthcare data. Our workflow is based on Bayesian networks, which are a popular tool for analyzing the interplay of biomarkers. Usually, data require extensive manual preprocessing and dimension reduction to allow for effective learning of Bayesian networks. For heterogeneous data, this preprocessing is hard to automatize and typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Their graphical representation allows for intuitive interpretation, also for non-experts. Based on the methodology described in an earlier study [ 28 ], we train a BN, including only those features that were identified as relevant in the RF model. To reduce the network’s complexity, we aggregated highly collinear features to represent them as one single node in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Their graphical representation allows for intuitive interpretation, also for non-experts. Based on the methodology described in an earlier study [ 28 ], we train a BN, including only those features that were identified as relevant in the RF model. To reduce the network’s complexity, we aggregated highly collinear features to represent them as one single node in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Since the BN in our case is defined over low dimensional representations of groups of variables, we call the structure Modular Bayesian Network (MBN). Notably, a MBN is a special instance of a hierarchical BN over a structured input domain [63][64][65][66].…”
Section: Modular Bayesian Networkmentioning
confidence: 99%
“…10,11 The proposed framework may also be useful for the novel and active research area of in-silico clinical trials, 12 for which generation of realistic virtual patients is a key consideration. While not in the context of the subject area explored in this study, Bayesian techniques have been widely used in biomedical engineering for network modelling, 13 uncertainty quantification, 14,15 parameter estimation and inference, [16][17][18][19][20][21][22][23][24][25] optimisation, 26 and optimal design. 27 This article is organised as follows.…”
Section: Introductionmentioning
confidence: 99%